(untitled) (Torani Journal of Fisheries and Marine Science, 2017)
Indonesia has a long costline dan have a high natural fisheries resources. One of natural resources from the coast area is seaweed. Seaweed is export commudity from fisheries sector and Indonesia is one of the third main producer for seaweed in the world. Seaweed species that have been cultured and utilized was only several species such as Glacillaria sp, Euchema cottoni and Geledium sp, on the other hand, Indonesia has a high diversity of seaweed. Based on LIPI data survey on 1998, it was found that 55 species of seaweed at Indonesian waters. Through this data, it showed that Indonesian water has a high potency for seaweed culture development. Aims of this study were to identify seaweed species that has a high potency to be cultured at South Sulawesi’s waters and to analyse natural potency of several seaweed species that can be cultured. Results study showed that diversity of seaweed species was varied within South Sulawesi’s waters. The highest number of species account for 30 species that found at Pangkep waters and the lowest number of species was found at Bone waters account for 5 species. There were three class of seaweed that found from locations, such as Red, Brown and Green algae. The highest number of species from Red algae class was found from Bantaeng waters, furthermore the highest number of species from brown algae class was found from Pangkep waters. Keywords : Seaweed, seaweed culture, South Sulawesi waters.